Analysis of Fried Bean Business Development in Lakanaha Village, Wadaga District, West Muna District - Sope, La; Rianda, La; Abdullah, Sukmawati (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2024)
This research aims to analyze the development of the fried bean business in Lakanaha Village, Wadaga District, West Muna Regency. The research location was determined purposively. Data collection was carried out using observation, questionnaires, interviews, and documentation methods. The analysis method used is Quality Function Deployment (QFD). The results of the research show that the development of fried bean products in the Lakanaha Village Fried Bean Business, using the QFD method, found that the priorities for development were in line with consumer expectations. The highest priority was packaging design (16.87%). The ability of business actors to develop fried peanut products includes sorting peanuts, the frying process, adding flavorings, making packaging, and marketing.